Influence of grandparents on the school process of grandchildren in a catholic school (Research, Society and Development, 2024)
It is understood that grandparents play a fundamental role in the lives of their grandchildren and living together can be pleasant for both with a strong legacy for generations. They are often seen as important figures in every way, including in relation to school learning, motivating and supporting school-age grandchildren, from getting them to school and helping them with homework. The main objective of our research was to describe the influence of grandparent-grandchild interaction in the educational context. This is a social survey that was carried out in a private school of the Catholic confession of grades I and II in the city of Salvador, Bahia, with 15 participants, 05 nuns, 05 specialists and 05 employees of the administrative and support team. We opted for the exploratory qualitative approach through semi-structured interviews. The results were organized in two main axes: profile of grandchildren and grandparents enrolled in the school context and the data resulting from the interviews were organized in the following themes: presence of grandparents: institutional issues and activities; influence of grandparents in the school process of their grandchildren. We conclude with the investigation that grandparents work on school tasks and influence the school performance.